(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted in Baghdad and aimed at the impact of cooperative learning on the achievement of biology and bullying behavior among second grade intermediate students. 26) students studied in the cooperative learning method, and the second division represented the control group (27) students studied in the usual way.